Financial Reporting and Audit Quality Impact on Investment Efficiency in Indonesian Transport and Logistics Companies - Chinhayu, Aziza; Saiful (Ilomata International Journal of Tax and Accounting, 2024)
The purpose of this research is to determine the impact of financial statement quality and audit quality on companies in the transportation and logistics sector listed on the Indonesia Stock Exchange during the period 2018 to 2022, especially in the transportation and logistics sector. Based on the issues of investment inefficiency in the company, research is conducted to provide managers with insights to consider investment decisions based on several variables influencing investment efficiency. The purpose of this research is to determine the impact of financial reporting quality and audit quality on investment efficiency on companies in the transportation and logistics sector listed on the Indonesia Stock Exchange during the period 2018 to 2022. By applying the purposive sampling method as a sampling technique, the data used in this research is 24 companies. The total data used in this research included 120 observations based on certain criteria. The analysis method applied is multiple linear regression analysis. And the results show that the quality of financial reporting and audit quality have a positive and significant influence on the company's investment efficiency decisions.